Jobs if you like science - Nardo, Don, 1947- (ReferencePoint Press, 2025)
"People interested in science early in life tend to have certain innate talents, some of which they develop into basic skills as they learn more about their chosen scientific branch. Those general abilities are most often classified as technical skills. Soft skills tend to be equally important as, or even more crucial than, hard skills for people looking for work in the field of science"--
Epidemiologist -- Computer hardware engineer -- Microbiologist -- Animal scientist -- Robotics engineer -- Environmental scientist.
Includes bibliographical references and index.
Ages 14-18.
Keywords: Science -- Vocational guidance -- Juvenile literature